Research progress on preparation methods of polyvinylidene - Lijuan YAN; Yajing XUN; Kunru MA; Yunlan SUN (Journal of Hebei University of Science and Technology)
Polyvinylidene difluoride (PVDF) has been demonstrated to possess considerable potential for significantly enhancing the ignition and combustion performance of boron and aluminum powders. Based on the extensive research on PVDF modified boron and aluminum energetic materials at home and abroad in recent years, ten mainstream techniques were summarized and refined, including solvent volatilization method, electrospinning technology, electrostatic spray technology, electrospray deposition method, microemulsion method, 3D printing technology, vacuum freeze-drying method, non-solvent induced phase separation method, liquid phase method and droplet microfluidic technology. Their preparation principles, application scenarios, advantages and disadvantages were described, the challenges of PVDF modified energetic materials were further pointed out, and the key directions for future research were proposed:1) safety improvements; 2) green technologies; 3) nanomaterial optimisation; 4) multi-scale design; 5) innovative coating methods; and 6) insight into reaction mechanisms.